Hibernating bat species of Belarus: results of the work of the Minsk bat contact centre - Shpak, A. (Theriologia Ukrainica, 2018)
Bat contact centres are organizations that exist in a number of countries and are engaged in popularization work, informational support for people facing bats, as well as rehabilitation and temporary maintenance of animals threatened with death during hibernation period. The data obtained during the activity of Minsk bat-contact centre during winter periods of 2007–2016 are presented in the article. In total, 108 hibernating specimens and 5 colonies of 6 species (V. murinus, N. noctula, E. nilssonii, E. serotinus, P. auritus, and P. kuhlii) were registered for 18 localities of Belarus. The dominant among the registered hibernating bats is V. murinus. At the same time, the expansion of the wintering range is shown for V. murinus, N. noctula, and P. kuhlii. The dynamics of the species registrations during the period of the activity of the Centre, as well as during the period of hibernation, are presented. The results of the Centre’s work show the high efficiency of such organizations for the monitoring of fauna and accumulation of scientific information. Контакт-центри по кажанам — товариства, які існують у низці країн і займаються популяризацією та інформуванням людей, які зіштовхнулися з рукокрилими, а також реабілітацією та зимовим утримуванням тварин, що знаходяться під загрозою загибелі впродовж гібернаційного періоду. У статті наведено дані, отримані Мінським контакт-центром щодо рукокрилим впродовж 2007–2017 рр. Всього відмічено 108 зимуючих особин та 5 колоній кажанів 6 видів (V. murinus, N. noctula, E. nilssonii, E. serotinus, P. auritus, P. kuhlii) з 18 населених пунктів Білорусії. Домінуючим у структурі зимуючих видів є лилик двоколірний. В той же час відмічено розширення зимівельного ареалу для трьох видів — V. murinus, N. noctula та P. kuhlii. Наведено як багаторічну, так і сезонну динаміку реєстрації тварин. Результати роботи Центру демонструють високу ефективність подібних центрів у моніторингу фауни і накопиченню наукової інформації.